Optimization Algorithms on Matrix Manifolds - Absil, P.-A; Sepulchre, R. (Rodolphe), 1967-; Mahony, R. (Robert), 1967- (Book collections on Project MUSE., 2008)
Many problems in the sciences and engineering can be rephrased as optimization problems on matrix search spaces endowed with a so-called manifold structure. This book shows how to exploit the special structure of such problems to develop efficient numerical algorithms. It places careful emphasis on both the numerical formulation of the algorithm and its differential geometric abstraction--illustrating how good algorithms draw equally from the insights of differential geometry, optimization, and numerical analysis. Two more theoretical chapters provide readers with the background in differentia.